ANALISIS KEPUASAN KERJA KARYAWAN CV. MITRA BELAWAN FISHING MEDAN - WILLIAM VINCENT; HARTONO .; WENY .; YULIANA .; NGAJUDIN NUGROHO (JURNAL ILMIAH KOHESI, 2019)
Job satisfaction is defined as a pleasant or unpleasant emotional state in which employees view their work. Job satisfactionreflects one's feelings about their work. This is seen in the positive attitude of employees towards work and everything that isencountered in the work environment. Employee job satisfaction must be created as well as possible so that employeemorale, dedication, love and discipline increase. The informants studied were employees at CV. Mitra Belawan FishingMedan. The research method used is a qualitative method where the data obtained is based on interviews with data sourcesused are primary data. The formulation of the problem in this study, "How is the job satisfaction of employees in theCV. Belawan Fishing Partner? The purpose of this research is to find out and analyze job satisfaction of employees in theCV. Mitra Belawan Fishing Medan. In this study, we can see in the background the problem of the existence of severalfactors that occur in the company that cause dissatisfaction in working, namely: the company gives wages not in accordancewith the UMR to employees, employees are only given a few allowances. From the results of these studies, the company hasseveral deficiencies in employee job satisfaction. With that the researcher wants to give some suggestions to improve jobsatisfaction of employees in the company.